Two novelties in genus Platystele (Orchidaceae: Pleurothallidinae) from Costa Rica - Karremans, Adam P.; Bogarín, Diego (Lankesteriana: International Journal on Orchidology, 2017)
Two new species of Platystele allied to P. oxyglossa complex are described from Costa Rica. Platystele carl-lueriana can be distinguished from P. catiensis and P. oxyglossa by the compact inflorescence that barely exceeds the leaf, from P. pedicellaris by the large plants with long leaves and small flowers, and from P. tausensis by the yellowish sepals and petals (vs. purple stained) and the minutely glandular (vs. apically hirsute) lip. The second species, Platystele jane-lueriana, can be easily distinguished by the glabrous flowers, and the conspicuously inflated, bulbous lip, with an incurved apex. Among the other members of the complex, it is most closely resembles P. pedicellaris in the compact inflorescence that is subequal to the leaves, but is distinguished by tail-less sepals and the linear-ligulate petals. With these additions, the total number of Costa Rican Platystele reaches twenty species.